Technical Efficiency of Cricket (A. domesticus and G.bimaculatus) Production: A Cobb-Douglas Stochastic Frontier Approach - Orinda, Mary Akinyi; Mosi, Reuben Oyoo; Ayieko, Monica Awuor; Amimo, Fred Anangwe; Nchimb, Hamisi Yunus (Journal of Agricultural Economics and Rural Development, 2018)
Technical efficiency measures the effectiveness of an enterprise given the available resources at disposal and how well it transforms these resources to get maximum output. This study therefore investigated the technical efficiency of cricket, A. domesticus and G. bimaculatus, production at JOOUST cricket farm using parametric approach. Stochastic frontier analysis was used to analyze the data collected from the farm between 2015-2017. Maximum likelihood estimates results indicated that labour, cotton wool and feed had significant effect on the technical efficiency of cricket production at 1% and 5% significant levels respectively. Species had significant positive (P<0.05) contribution to inefficiency while scale of production and experience had significant negative contribution to technical inefficiency at 5% and 1% significant level respectively. Production in the farm was characterized by decreasing returns to scale implying that labour saving technologies combined with proper feeding rates and cheap alternative to inputs such as cotton wool should be considered. In addition, production scale should be expanded to contribute to efficiency through the benefits of economies of scale. However, further research should be done on allocative efficiency to permit a rational and comprehensive economic efficiency conclusion.
Keywords: Cricket; Cobb-Douglas; Technical Efficiency; Stochastic Frontier Approach; Production